Proteinase-α-2-Macroglobulin Balance Under Immersion and Craniocerebral Hypothermia - Lomako, Viktoria; Samokhina, Lubov (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(1):050–054